Night eating among veterans with obesity. (1st October 2017) - Dorflinger, Lindsey M.; Ruser, Christopher B.; Masheb, Robin M.
Abstract: The obesity rate is higher among veterans than the general population, yet few studies have examined their eating behaviors, and none have examined the presence of night eating and related comorbidities. This study examines night eating syndrome (NES) among veterans seeking weight management treatment, and relationships between NES and weight, insomnia, disordered eating, and psychological variables. The sample consisted of 110 veterans referred to a weight management program at VA Connecticut Healthcare System. More than one out of ten veterans screened positive for NES, and one-third screened positive for insomnia. Most individuals screening positive for NES also screened positive for insomnia. Night eating was associated with higher BMI, and with higher scores on measures of binge eating, emotional overeating, and eating disorder symptomatology. Veterans screening positive for NES were also significantly more likely to screen positive for depression and PTSD. When controlling for insomnia, only the relationships between night eating and binge and emotional eating remained significant. Those screening positive for PTSD were more likely to endorse needing to eat to return to sleep. Findings suggest that both NES and insomnia are common among veterans seeking weight management services, and that NES is a marker for additional disordered eating behavior, specifically binge eating and overeating in response to emotions. Additional studies are needed to further delineate the relationships among NES, insomnia, and psychological variables, as well as to examine whether specifically addressing NES within behavioral weight management interventions can improve weight outcomes and problematic eating behaviors.